Can salivary and skin microbiome become a biodetector for aging-associated diseases? Current insights and future perspectives - Nurkolis, Fahrul; Utami, Trianna Wahyu; Alatas, Aiman Idrus; Wicaksono, Danar; Kurniawan, Rudy; Ratmandhika, Satria Rafi; Sukarno, Kartika Taufani; Pahu, Yehezkiel Gian Pradipta; Kim, Bonglee; Tallei, Trina Ekawati; Tjandrawinata, Raymond Rubianto; Alhasyimi, Ananto Ali; et al. (Frontiers in Aging, 2024)
Growth and aging are fundamental elements of human development. Aging is defined by a decrease in physiological activities and higher illness vulnerability. Affected by lifestyle, environmental, and hereditary elements, aging results in disorders including cardiovascular, musculoskeletal, and neurological diseases, which accounted for 16.1 million worldwide deaths in 2019. Stress-induced cellular senescence, caused by DNA damage, can reduce tissue regeneration and repair, promoting aging. The root cause of many age-related disorders is inflammation, encouraged by the senescence-associated secretory phenotype (SASP). Aging’s metabolic changes and declining immune systems raise illness risk via promoting microbiome diversity. Stable, individual-specific skin and oral microbiomes are essential for both health and disease since dysbiosis is linked with periodontitis and eczema. Present from birth to death, the human microbiome, under the influence of diet and lifestyle, interacts symbiotically with the body. Poor dental health has been linked to Alzheimer’s and Parkinson’s diseases since oral microorganisms and systemic diseases have important interactions. Emphasizing the importance of microbiome health across the lifetime, this study reviews the understanding of the microbiome’s role in aging-related diseases that can direct novel diagnosis and treatment approaches.